Incidência e fatores associados as quedas de idosos hospitalizados - Abreu, Hellen Cristina de Almeida (2014)
The increasing growth in number of people aged 60 and over in Brazil has resulted in changes in the morbidity and mortality of this population profile. Among the problems that contribute to it, falls is the most prevalent. In general, hospitalized elderly fall more frequently than those living in the community. In order to analyze the incidence of falls in hospitalized elderly and its associated factors a prospective cohort study was conducted from March to August 2013 Grosso with 221 people aged 60 years or older admitted in medical clinic in three hospitals in the city of Cuiabá, Mato. The participants were followed until discharge, death or fall. We used the method of incidence density to calculated the incidence rate. The bivariate analysis was by chi –square and multiple by Cox regression analysis. The incidence of falls was 12.6 per 1000 patient-days. Predictive factors for falls during hospitalization were low education (RR = 2.48, 95% CI 1.17 to 5.25), polypharmacy (RR = 4.42, 95% CI 1.77 to 11.05), visual dysfunction (RR = 2.06, 95% CI 1.01 to 4.23), gait/ balance dysfunction (RR = 2.95, 95% CI: 1.22 to 7.14), urinary incontinence (RR = 5.67, 95% CI 2.58 to 12.44), use of laxatives (RR = 4.21, 95% CI 1.15 to 15.39) and use of antipsychotics (RR = 4.10, CI95 %: 1.38 to 12.13). In order to analyze the effect of urinary incontinence as a predictor of the incidence of falls among elderly hospitalized Survival analysis and verification of the association between the exposure variable and other variables was performed using the Kaplan -Meier, incidence density and Cox regression model. Urinary incontinence was a strong predictor of falls in the elderly and associated with shorter time to occurrence of the event. The urinary incontinence concomitant to the balance/gait dysfunction and use of antipsychotics were associated with falls. We concluded that, in this study, the incidence of falls in hospitalized elderly patients was high, therefore measures to prevent the risk of falls in hospitals is needed to reduce the incidence of this event, especially to patients with urinary incontinence.